Foreign direct investment‐firm productivity nexus in West Africa: New empirical insights from firm level data. Issue 4 (10th March 2021) - Orji, Anthony; Aza, Gabriel Chiangi; Anthony‐Orji, Onyinye I.; Isaac, Ndubuisi
Abstract : As recorded widely in the extant literature, foreign‐invested firms with superior technology and managerial skills are likely to generate productivity spillovers that may be beneficial to local firms. We examine firm level productivity spillovers in the West African context. Four countries were sampled on the basis that they share institutional and similarities as British colonies and social economic similarities as West African countries. The Levinshon and Petrin methodology was fitted with firm level data sourced from the World Bank enterprise survey for the period 2006–2018 with the sampled countries having data for different years. Our results confirm that foreign direct investment has a significant and positive impact on the productivity of firms in West Africa. Controlling for other effects, Capital intensity has a significant but negative effect on firm productivity; changes in market concentration do not have any impact while firm size negatively affects productivity of firms in the region. The study recommends among other things that policy should be targeted towards removing all cumbersome access restrictions experienced by foreign investors. Improvement in the ease of doing business in these countries could be a major policy thrust which will clear up the path of direct investment inflow.